2014
DOI: 10.5146/tjpath.2014.01270
|View full text |Cite
|
Sign up to set email alerts
|

Intraoperative frozen section in ovarian neoplasms; a tertiary center experience

Abstract: Objective: Frozen section is an accurate diagnostic tool with some unavoidable pitfalls in gynecologic tumors. We aimed to evaluate the diagnostic value of frozen section, and to detect the factors causing erroneous diagnosis in ovarian tumors. Material and Method:Frozen section and paraffin section reports of 282 patients with ovarian neoplasms diagnosed between July 2006 and January 2013 in our institute were re-analyzed. Results were grouped into benign, borderline (for epithelial tumors) and malignant cate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 16 publications
(12 reference statements)
3
4
0
Order By: Relevance
“…In another retrospective review of 282 cases, sensitivities of the frozen section for benign, borderline, and malignant tumors were 97.5, 95.8, and 95.6 %, and corresponding specificities were 97.5, 97.6, and 100 %, respectively. They found the lowest positive predictive value in borderline group (79.3 %), all of them with mucinous type epithelium as described by other authors [ 9 ]. Another oncology center reported an overall accuracy of 91.85 %.…”
Section: Discussionsupporting
confidence: 59%
“…In another retrospective review of 282 cases, sensitivities of the frozen section for benign, borderline, and malignant tumors were 97.5, 95.8, and 95.6 %, and corresponding specificities were 97.5, 97.6, and 100 %, respectively. They found the lowest positive predictive value in borderline group (79.3 %), all of them with mucinous type epithelium as described by other authors [ 9 ]. Another oncology center reported an overall accuracy of 91.85 %.…”
Section: Discussionsupporting
confidence: 59%
“…Given the low accuracy rate for borderline ovarian tumors, care and attention are required to develop this field (10,11,13,14,18). Most studies typically reported a sensitivity of 71-100% for the detection of malignancies by frozen section, and a specificity ranging from 96-100% (11,19,21,23,26,27). In our study, the sensitivity of malignant ovarian tumor detection was 93.3% and the specificity was 100%, reflecting that the frozen section examination was highly sensitive and specific to ovarian malignancy.…”
Section: Discussionsupporting
confidence: 54%
“…In a review of 60 patients of ovarian tumors by(11), frozen section had low sensitivity (75%) and PPV (50%) for borderline tumors. In a further retrospective study of 282 cases, the sensitivity of the frozen section to borderline tumors was 95.8% and the specificity 97.6%(23). For the borderline category, they found the lowest positive predictive value (79.3%), all with epithelium of mucinous type.…”
mentioning
confidence: 88%
“…Various studies have compared the diagnostic accuracy of SS and FS with final histopathological diagnosis. [12345678910111213] The benefits of intaoperative diagnosis by cytomorphology over FS have been described. SSs are less time-consuming, inexpensive, and lack freezing artefacts; various heterogeneous areas can be examined in little time and tissue loss can be avoided.…”
Section: Discussionmentioning
confidence: 99%
“…The possible reason for discordance between FS and HPE in mucinous tumors is associated with characteristics of these tumors such as larger sizes and presence of benign, borderline, and malignant components in the same tumor in contrast to serous tumors. [9101112] The sampling thus should be done from solid-looking areas of cystic neoplasms. In addition, metastatic tumors especially mucinous carcinomas maybe challenging in FS if there is inadequate clinical information and communication with the surgeon.…”
Section: Discussionmentioning
confidence: 99%